The bell jar a novel - Plath, Sylvia; Ahmed, Islam (Cairo alkenzy publishing, 2024)
The bell jar chronicles the creck-up of esther greenwood, young, brilliant, beautiful, and enormously talented, but slowly going under- maybe for the last time, Sylvia Path masterfully draws the reader into Easther's breakdown with such intensity that easther's neurosis becomes completely understanable and even rational, as probable and accessible an experience as going to the movies, such thorough exploration of the dark and harrowing corners of the psyche-and the profound collective loneliness that modern society has yet to find a solution for is an extraordinary accomplishment, and has made the Bell Jar a haunting ammerican classic
The best selling novel in the world
11
Keywords: Depression, Mental -- Fiction; Mental illness -- Fiction; Women college students -- Fiction